1973
DOI: 10.1002/pssa.2210160133
|View full text |Cite
|
Sign up to set email alerts
|

Critical temperature of superconducting transition in plastically deformed rhenium single crystals

Abstract: The effect of tensional plastic deformation and of defects produced during this process on the change in temperature (Tc) of the superconducting transition of Re single crystals has been considered. The Tc dependence on the degree of plastic deformation has been obtained for different deformation temperatures and crystal orientations. Electron microscopy show that the defect structure of deformed Re is characterized by the presence of planar defects, i.e. a combination of slip bands and twin layers, between wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Similar to previous studies [1,2], the work here has shown that {1121} twinning is a dominant deformation mode in Re. The dominant grain orientations, with the [0001] oriented perpendicular to the compression direction, would also encourage the observed twinning behavior.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar to previous studies [1,2], the work here has shown that {1121} twinning is a dominant deformation mode in Re. The dominant grain orientations, with the [0001] oriented perpendicular to the compression direction, would also encourage the observed twinning behavior.…”
Section: Discussionsupporting
confidence: 90%
“…This extensive twinning is likely responsible for much of rhenium's ductility, as well as a large contributing factor to its high work hardening rate as the twin planes create barriers to further dislocation and twinning-based plasticity. Many of the previous studies of Re have been limited to deformation of single crystals [1,5]. This study has shown the important role of grain boundaries in relation to twin deformation, with high angle grain boundaries providing much stronger barriers to twin propagation than low angle grain boundaries.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations